2022
DOI: 10.1186/s13017-022-00438-8
|View full text |Cite
|
Sign up to set email alerts
|

The uniportal VATS in the treatment of stage II pleural empyema: a safe and effective approach for adults and elderly patients—a single-center experience and literature review

Abstract: Background Pleural empyema (PE) is a frequent disease, associated with a high morbidity and mortality. Surgical approach is the standard of care for most patients with II-III stage PE. In the last years, the minimally invasive surgical revolution involved also thoracic surgery allowing the same outcomes in terms of safety and effectiveness combined to better pain management and early discharge. The aim of this study is to demonstrate through our experience on uniportal-video-assisted thoracosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Matsudaira et al reported VATS timing for acute pyothorax but no speci c phase (19). For phase-speci c studies, such as the study by Luciani et al on uniportal VATS in the treatment of stage II pleural empyema, "surgery at days after admission" was used to standardize treatment timing (20). Similarly, for our particular group and focus, we choose a more speci c and objective index -duration to surgery since admission day.…”
Section: Discussionmentioning
confidence: 99%
“…Matsudaira et al reported VATS timing for acute pyothorax but no speci c phase (19). For phase-speci c studies, such as the study by Luciani et al on uniportal VATS in the treatment of stage II pleural empyema, "surgery at days after admission" was used to standardize treatment timing (20). Similarly, for our particular group and focus, we choose a more speci c and objective index -duration to surgery since admission day.…”
Section: Discussionmentioning
confidence: 99%
“…Another key point is absence of a systematic classification that includes BDTT as a prognostic factor. These two points do not allow clinicians to appropriately relate BDTT to a stage of HCC; however, surgical treatment appears to be the first treatment option [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Considering the undeniable benefits of minimally invasive surgery, we have to underline that it offers a safer surgical approach for patients with a Performance Status (PS) of 1 or 2, allowing a shorter length of stay and faster recovery which as show a great impact also in patients undergoing surgical downstaging [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, Komici et al [102] evaluated the prevalence and impact of frailty in HPB surgery: Frailty was found in about 40% of patients affected by liver cancer, including CRLM. Indeed, comorbidities and frailty should be managed in elderly patients to predict inter-individual variability [103,104]. It is a crucial point: an early detection of CRLM could improve long-term outcomes in this subset of patients, considering the mortality rate reported for major hepatectomies [71,105].. Future perspectives are linked to AI applications to predict liver failure or future liver remnants in the preoperative evaluation of patients affected by huge liver tumors [106,107].…”
Section: Chemotherapy Regimenmentioning
confidence: 99%